Analysis of the Influence of Product Quality, Service Quality and Company Image on Customer Loyalty through Customer Satisfaction as an Intervening Variable at PT BPR BKK Lasem (Perseroda) - Herry Setyo Nugroho; Mochamad Edris; Sutono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of product quality, service quality, company image on customer satisfaction and to analyze the influence of product quality, service quality, company image on customer loyalty. customer loyalty of PT BPR BKK Lasem (Perseroda. The population of this research is 57,196 customers, consisting of 54,468 savings customers and 2,728 deposit customers. And the technique used is purposive sampling with a sampling number of 155 respondents. The data analysis method in this research can shows a model that explains the simultaneous relationship between variables. Data analysis in research uses the Strutural Equation Modeling (SEM) program. Conclusions from research on product quality, service quality, company image have a positive and significant effect on customer satisfaction at PT BPR BKK Lasem (Perseroda) .